Efficacy and safety of topical JTE‐052, a Janus kinase inhibitor, in Japanese adult patients with moderate‐to‐severe atopic dermatitis: a phase II, multicentre randomized, vehicle‐controlled clinical study. (1st February 2018) - Nakagawa, H.; Nemoto, O.; Igarashi, A.; Nagata, T.
Summary: Atopic dermatitis (eczema) is a chronic, and sometimes debilitating, inflammatory skin disease which causes itching and damaged skin barrier function. Current treatments include topical (applied to the skin) corticosteroids and calcineurin inhibitors such as tacrolimus; unfortunately long‐term use of topical corticosteroids may cause thinning of the skin and tacrolimus can be irritant. Kinases are enzymes that are important to many roles of cells within the body, and the Janus Kinase (JAK) pathway plays a role in inflammation. In recent years, medicines that inhibit this pathway have been developed, with potential benefit in inflammatory skin diseases such as eczema or psoriasis. The authors, based in Tokyo and Hokkaido, Japan, studied the effect of different concentrations (0.5‐3%) of a topical JAK inhibitor, JTE‐052, in adults with moderate to severe atopic dermatitis, compared with the vehicle on its own (the ointment to which the medicine is added), and with 0.1% tacrolimus ointment. They used a modified Eczema Area and Severity Score before and after 4 weeks of treatment to allow them to see how well each of the treatments was working. In the patients using the 3% concentration there was 73% improvement in the score, compared with 12% using the placebo (vehicle) ointment. There was a 62% improvement in the patients using tacrolimus. Even the 3% concentration of JTE‐052 was very well tolerated, without the irritancy and burning seen with tacrolimus, and the patients using JTE‐052 noticed a reduction in itching within a day of starting treatment. The authors conclude that topical use of this JAK inhibitor is effective in the treatment of atopic dermatitis.